2020
DOI: 10.1177/0022034520962728
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of WNT10A Rare Variants Associated with Tooth Agenesis

Abstract: Mutations in WNT10A have frequently been reported as etiologic for tooth agenesis (TA). However, the effects of WNT10A variation on gene/protein function and contribution to TA phenotypes remain poorly understood. Here, we performed bioinformatic and functional characterization analysis of WNT10A variants. In silico prediction of variant function was performed with VIPUR for all WNT10A missense variants reported in the Exome Aggregation Consortium database. Functional characterization experiments were then per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…WNT10A mutants were found to inhibit Wnt signalling and dysregulate the expression levels of genes involved in protein folding and stability (Y. Zeng et al, 2021). The nonsense WNT10A mutation c.742C > T (p.R248*) detected in family 1 has been reported in two nonconsanguineous patients, one with nonsyndromic TA (B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WNT10A mutants were found to inhibit Wnt signalling and dysregulate the expression levels of genes involved in protein folding and stability (Y. Zeng et al, 2021). The nonsense WNT10A mutation c.742C > T (p.R248*) detected in family 1 has been reported in two nonconsanguineous patients, one with nonsyndromic TA (B.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in WNT10A were further identified as common causative factors contributing to the aetiology of TA (van den Boogaard et al, 2012). WNT10A mutants were found to inhibit Wnt signalling and dysregulate the expression levels of genes involved in protein folding and stability (Y. Zeng et al, 2021). The nonsense WNT10A mutation c.742C > T (p.R248*) detected in family 1 has been reported in two nonconsanguineous patients, one with nonsyndromic TA (B. Zeng et al, 2017) and the other with OODD (Yu, Liu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…WNT10A is a member of the WNT gene family, which is clustered in the 2q35 region on human chromosomes ( 8 ). It has been confirmed that WNT10A mutation plays an important role in tooth dysplasia and ectoderm dysplasia ( 9 – 11 ), and WNT10A is highly expressed in a variety of malignant tumors, such as thyroid cancer, ovarian cancer, esophageal squamous cell carcinoma, renal cell carcinoma, and colorectal cancer ( 12 16 ). Dong et al ( 12 ) indicated that WNT10A may plays a crucial role in carcinogenesis and aggressiveness in papillary thyroid cancer by activating β-catenin-dependent pathway.…”
Section: Introductionmentioning
confidence: 98%
“… 56 , 57 mediation of dentinogenesis. 58 , 59 VPS4B Regulate tooth development. 60 Shh Signaling Pathway Shh Shh regulates growth and determines the shape of the tooth.…”
Section: Introductionmentioning
confidence: 99%